Lectotypification of the name Scrophularia tenuipes Coss. (Scrophulariaceae) - El Mokni, Ridha; de Belair, Gerard; Domina, Gianniantonio (Phytotaxa, 2019)
The present contribution is part of an ongoing project for the investigation of the Algerian-Tunisian Flora (see e.g., El Mokni et al. 2014, 2015a, 2015b, 2015c; El Mokni & Iamonico 2018, El Mokni & Domina 2019). Special attention is dedicated to the endemic component of this flora and its type localities (loci classici), that are considered a rich source of biogeographical information (Brundu et al. 2015).